Determinants of Saving and Investment Behavior of Rural People in Chaukune Rural Municipality, Surkhet District - Gautam, Ramesh Prasad (Journal of Nepalese Management and Research, 2023)
This study determines the saving and investment behavior determinants of rural people in Chaukune Rural Municipality, Surkhet district. The research mainly applied primary sources to collect the data required in the study. Among the population, 180 respondents are selected as the sample size using convenience sampling. The study applied a quantitative research method and is based on positivist philosophy. The entire questionnaire is prepared based on the Likert scale. Collected data is processed using a statistical regression analysis tool. Based on multivariate regression analysis, most independent variables significantly impact the dependent variable, i.e., financial literacy, investment motive, and saving culture, which significantly positively impact saving and investment behavior.